2011
DOI: 10.1007/s10551-011-1105-5
|View full text |Cite
|
Sign up to set email alerts
|

The Shareholder–Manager Relationship and Its Impact on the Likelihood of Firm Bribery

Abstract: We examine the impact on firm bribery of two corporate governance devices heavily studied in corporate governance research-i.e., separation of ownership and control, and equity share of the largest shareholder. In addition, we investigate the impact of the principal-owner's gender on firm bribery. From agency theory, we predict that firms with the owner also acting as a manager (owner-manager) are more likely to engage in bribery compared to their counterparts with separation of ownership and control. We argue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 60 publications
0
57
0
Order By: Relevance
“…This finding is similar to those of previous related studies. For example, Ramdani and van Witteloostuijn () found that male principal owners of firms were more likely to engage in bribery than their female counterparts are. Furthermore, Swamy et al .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to those of previous related studies. For example, Ramdani and van Witteloostuijn () found that male principal owners of firms were more likely to engage in bribery than their female counterparts are. Furthermore, Swamy et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Clarke and Xu (2004) used samples from Eastern Europe and Central Asia and found that profitable firms are more likely to bribe. Ramdani and van Witteloostuijn (2012) reported that the separation of ownership and control is associated with a firm's likelihood to bribe. In addition, firm characteristics, such as growth rate, firm size, and corporate governance, are important factors when predicting firm bribery activity (Wu, 2009).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Agency theory suggests that the conflict between the principle and the manager of a firm comes from the different goals of these two parties. For a firm's board of directors, the main goal is to protect shareholders' interests and maximize the value of the firm (Ramdani & van Witteloostuijn, 2012); they are more interested in pursuing strategies for long-term profits. For shareholders, although bribery might bring them short-term profits, engaging in bribing activities might also jeopardize the long-term interests of the firm.…”
Section: Firm-level Hypothesis: Mcfs Vs Shareholder-controlled Firmsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the study does not address completely how the different kinds of corruption and lobbying interact with each other. Ramdani and Witteloostuijn (2012) predict that bribery is more likely to occur when the principal-owner is male rather than female. Using the World Bank Enterprise Surveys of 2002-2005 they found that the equity share of the largest shareholder is negatively related with the likelihood of firm bribery.…”
Section: Literature Reviewmentioning
confidence: 99%